PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA PASIR JAYA KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Mahendra Kurniawan; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Indonesia is a developing country, so development is echoed in various aspects in the interests of equitable development and human welfare. In order to achieve the expected development, public participation in these development activities is required. Community involvement in development means the voluntary participation of the community in the processes of the development activities carried out. In this study, researchers examine the phenomenon of public participation in infrastructure development in Pasir Jaya Village, Rambah Hilir District, Rokan Hulu Regency linked to the Village Fund. The theory used in this research is rational choice theory. To examine the data obtained, the author uses qualitative research methods with data collection methods through observation, interviews, and documentation. The data supporting this research are divided into primary and secondary data. The results of this study suggest that the Village Fund Allocation in Pasir Jaya Village is based on Village Law No. 6 of 2014 and based on the Permendesa. In addition, the results of this study show that participation in development in Pasir Jaya Village is high in the operational dimension with personnel involvement and fruit utilization in the economy, on the one hand development certainty in Pasir Jaya Village is also low in providing ideas and funds donate.Keywords: Village Fund, Participation, Infrastructure Development